2011
DOI: 10.3390/molecules17010080
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Lillium candidum L. Can Modulate the Genotoxicity of the Antibiotic Zeocin

Abstract: Lilium candidum L. extract (LE) is well known in folk medicine for the treatment of burns, ulcers, inflammations and for healing wounds. This work aims to clarify whether the genotoxic potential of the radiomimetic antibiotic zeocin (Zeo) could be modulated by LE. Our results indicate that LE exerts no cytotoxic, DNA-damaging and clastogenic activity in in Chlamydomonas reinhardtii, Pisum sativum L. and Hordeum vulgare L. test systems over a broad concentration range. Weak but statistically significant clastog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In our study, the protective effect was shown to depend on the experimental design and the test systems. The data correlate with the results for whole L. candidum extract (Kopaskova et al, ), suggesting that jatropham and kaempferol most probably play a key role in the protective effect. The antimutagenic effect of the whole Lilium extract in barley appears to depend to a greater extent on the experimental design, which could be due to other compounds.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In our study, the protective effect was shown to depend on the experimental design and the test systems. The data correlate with the results for whole L. candidum extract (Kopaskova et al, ), suggesting that jatropham and kaempferol most probably play a key role in the protective effect. The antimutagenic effect of the whole Lilium extract in barley appears to depend to a greater extent on the experimental design, which could be due to other compounds.…”
Section: Discussionsupporting
confidence: 87%
“…On the basis of our preliminary experiments with the whole Lilium extract (Kopaskova et al, ), the most appropriate concentration ranges, treatment times and experimental designs were applied for both test systems. The concentration of jatropham and kaempferol used in H. vulgare was 100 μg mL −1 and in human lymphocytes, 10 μg mL −1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the highly efficient ones are natural herbal extracts that comprise polyphenolic compounds. Natural plant extracts are now gaining more pharmacological attention, as many previously unexplored plant species appear to demonstrate a wide range of activities, such as anti-cancer activities (Vitalone et al 2003a(Vitalone et al , 2003b(Vitalone et al , 2006Scheck et al 2006), DNA protective and antimutagenic activities (Miadokova et al 2010;Kopaskova et al 2011), anti-inflammatory activities (Talhouk et al 2007), and anti-aging activities (Kim et al 2004). Among them are extracts from the aerial parts of Epilobium angustifolium (EA) (Oenotheraceae).…”
Section: Introductionmentioning
confidence: 99%